2009
DOI: 10.1016/j.ejpain.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of spinal cord glial cells in murine models of neuropathic and cancer pain

Abstract: Activation of spinal cord microglia and astrocytes is a common phenomenon in nerve injury pain models and is thought to exacerbate pain perception. Following a nerve injury, a transient increase in the presence of microglia takes place while the increased numbers of astrocytes stay elevated for an extended period of time. It has been proposed that activated microglia are crucial for the development of neuropathic pain and that they lead to activation of astrocytes which then play a role in maintaining the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 44 publications
12
102
1
Order By: Relevance
“…It has been shown using OX-42, a microglial activation marker, and GFAP, an astrocytic activation marker, that early spinal microglial activation and delayed spinal astrocytic activation follow nerve injury/ inflammation (9,11,12). Even after microglial activation begins to decrease, astrocytic activation persists, as does neuropathic pain (13). This temporal pattern is further confirmed by sequential activation of mitogen-activated protein kinase (MAPK) / extracellular signal-regulated kinase (ERK) in microglia and then in astrocytes following spinal nerve ligation (SNL) (14).…”
Section: Activation Of Spinal Microglia and Astrocytes In Pathologicamentioning
confidence: 99%
“…It has been shown using OX-42, a microglial activation marker, and GFAP, an astrocytic activation marker, that early spinal microglial activation and delayed spinal astrocytic activation follow nerve injury/ inflammation (9,11,12). Even after microglial activation begins to decrease, astrocytic activation persists, as does neuropathic pain (13). This temporal pattern is further confirmed by sequential activation of mitogen-activated protein kinase (MAPK) / extracellular signal-regulated kinase (ERK) in microglia and then in astrocytes following spinal nerve ligation (SNL) (14).…”
Section: Activation Of Spinal Microglia and Astrocytes In Pathologicamentioning
confidence: 99%
“…The concept of "functional islands of synapses" highlights the vital roles astrocytes play in the modulation of neuronal function by synchronizing neuronal firing and coordinating synaptic networks [41] . A study using mice demonstrated that the activation of astrocytes, but not microglia, was a prerequisite in two types of cancer-induced pain models [42] . Therefore, reactive astrocytes play a crucial role in BCP.…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
“…Micro-CT in vitro scanning has been widely used for bone samples obtained from all sizes of animal, such as mouse [2,[75][76][77], rat [175], guinea pig [44], rabbit [52,149], dog [28,46,85,101,102], pig [106,107] sheep [7,37], and human [29,51,[64][65][66][67]. In vivo micro-CT imaging can now also be applied to all sizes of animals depending on the location to be scanned.…”
Section: ) In Vivo Micro-ct For Animal Researches and For Humanmentioning
confidence: 99%